Issues and Challenges of Providing Online Inservice Teacher Training: Korea's experience - Insung Jung (International Review of Research in Open and Distributed Learning, 2001)
To meet the need for flexible and interactive teacher training, the Korean government created a Cyber Teacher Training Center (CTTC) in the summer of 1997. The CTTC project developed a software platform for managing online inservice teacher training, eleven general training courses, with plans to add more courses each year. This article examines the needs met through the introduction of online inservice teacher training and the strategies that have been employed in the process. This paper also analyzes the major impacts of online teacher training and looks at the challenges facing online inservice teacher training in the coming years.